VIABILITAS SEMEN SAPI SIMENTAL YANG DIBEKUKAN MENGGUNAKAN KRIOPROTEKTAN GLISEROL - Muhamad Ilyas Mumu (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
This experiment used semen from a Simental bull, age 4 years old, 850 kg in weight and was healthy especially his reproduction organ.  Semen collection was done twice a week using an artificial vagina.  Soon after the semen was evaluated, it was diluted with tris aminomethan plus egg yolk and three concentration of glycerol namely 3% (G1), 5% (G2) and 7% (G3).  The semen was packed in 0.25 ml straw and maintained in equilibrium at 5oC for 4 hours and frozen in liquid nitrogen for 60 minutes.  Data collected were motility and percentage of living spermatozoa after freezing.  The experiment used a Completely Randomized Block Design.  The results showed that motility and percentage of living spermatozoa after freezing for each treatment were not significant (P>0.05).  The effect of those three treatments on motility and percentage of living spermatozoa after freezing were 40.2% and 59.6% for G1, 41.2% and 63.8% for G2 and 39.8% and 57.8% for G3, respectively, but the G2 treatment was better in protecting the quality of the spermatozoa than the other treatments. It was appeared that the level of glycerol at 5% concentration is an optimal dosage for maintaining the quality of the frozen semen